Improvement of output current waveforms using SVM technique and fuzzy logic controller for matrix converter. Issue 6 (2nd November 2015) - Boukadoum, Aziz; Bahi, Tahar; Soufi, Youcef; Bouguerne, Abla; Oudina, Sofiane
Abstract : Purpose: – The use of power electronic equipment such as conventional AC-DC-AC converters cause several problems in electrical networks and its components. They generate harmonic currents and disturb the electrical power sources; so, it is necessary to research alternative topologies of power electronic converters based on advanced intelligent controllers, which reduce or even eliminate harmonics to achieve energy-saving and environmental protection. The use of matrix converter (MC) is, considered as an attractive solution to maintain pure sinusoidal input and output current waveforms. The paper aims to discuss this issue. Design/methodology/approach: – The studied system is composed of a three phase matrix converter (TMC) feeding a linear R, L load and a trees phase rectifier considered as a non-linear load; the proposed control strategy is based on a fuzzy logic controller (FLC) associated to the (space vector modulation) SVM modulation technique, this choice is motivated by the advantages that represent the combination of FLC and SVM in term of power quality enhancement in both input and output sides of MC. Findings: – The model is validated based on simulation results that illustrate the effectiveness of the proposed system in term of power quality amelioration. The high performance of the proposed FLC is illustrated in all study cases especially in the case of perturbed input voltage, it is not only able to keep the whole system stable, but also it reduces harmonic distortion THD to respect international standards recommendation. Originality/value: – In this paper, an associated linear (RL), non-linear loads and TMC is studied. From the mathematical point of view, the MC is modeled and analyzed. From the technique point of view, the MC allows sinusoidal current absorbance from the network with good qualities in term of harmonic distortion compensation, and high reliability under various loads and disturbed input voltage.